Ethnographic Documentary as a Translator of Architecture and Urban Research: Perspectives on an Australian-Italian Intercultural Experience. (2nd January 2020) - Rose, Cameron; Alexander, Jacqui; Grassi, Samuele
Abstract: Video is becoming an important tool when investigating and communicating architectural and urban design research. From social research of a site before design, the lived experience of a completed structure, to the communication of architectural projects, video functions as an effective means of capturing and disseminating qualitative data. This paper presents findings from an Australian-Italian collaboration that produced five short documentaries by Australian architecture students on the lived urban experience of residents and businesses in Prato, Italy. It asks: what are the opportunities and challenges of video ethnography as a research practice in design education? In answering this question, the paper provides three disciplinary perspectives on the project: examining the pedagogical objectives and the potential for this approach to catalyse actual change in the world, the methodology for using video and sensory ethnography techniques in capturing and editing qualitative data, and the importance of collaboration with an Italian translator in the design of culturally appropriate questions and the production of videos. Finally, the paper reflects on the documentary outcomes and learning experience, to discuss the value of this intercultural approach for design education and by extension, practice.